2017
DOI: 10.1111/are.13565
|View full text |Cite
|
Sign up to set email alerts
|

Changes in proximate composition, lipid class and fatty acid profile in Greenshell™ mussels (Perna canaliculus) over an annual cycle

Abstract: Greenshell TM mussel (GSM, Perna canaliculus) is New Zealand's most important aquaculture species. This study looked at changes in the proximate composition, lipid class and fatty acid profile of male and female market ready mussels over a year from April 2016 through to March 2017. There were differences over the season as well as differences between male and female mussels. Winter GSM had lower lipid, carbohydrate and protein concentrations than other seasons. Female mussels had a higher lipid (on average 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…One of the major advantages of FT‐NIRs predictive models is the reduction in cost per sample and the higher throughput of samples. Particularly in GSM, we have seen large individual variability in mussels grown in the same areas and harvested at the same times (Miller, Pearce, & Bettjeman, ; Miller & Tian, ). Brown et al () completed a cost‐benefit analysis of NIRs on oysters and showed a cost reduction in between US$57 and US$6 per sample, depending on the number of samples assessed per calendar year.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One of the major advantages of FT‐NIRs predictive models is the reduction in cost per sample and the higher throughput of samples. Particularly in GSM, we have seen large individual variability in mussels grown in the same areas and harvested at the same times (Miller, Pearce, & Bettjeman, ; Miller & Tian, ). Brown et al () completed a cost‐benefit analysis of NIRs on oysters and showed a cost reduction in between US$57 and US$6 per sample, depending on the number of samples assessed per calendar year.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the work reported in this paper we attempted to determine parameters and develop a calibration for fatty acid (FA) profiles for both GSM and king salmon. In the case of GSM, the content of fat was relatively low (0.8–2.4 g/100 g) and therefore fatty acid composition such as omega‐3 content or docosahexaenoic acid (DHA, 22:6n‐3) and eicosapentaenoic acid (EPA, 20:5n‐3) was even lower (Miller & Tian, ). The models developed for these parameters were not optimal as no defined peaks in the spectrum, outside of the C‐H stretch peak, could be identified to be attributed solely to the polyunsaturated fatty acids (such as a C = C stretch).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations